Study on the response mechanism of the Yellow River delta region to the cold wave process - Shi, Hongyuan; Ma, Pengcheng; Sun, Jiwei; Zhao, Shengnian; Ma, Ruiqian; Li, Longsheng; Zhan, Chao; Liang, Hui (Frontiers in Marine Science, 2024)
Cold waves, as a common natural disaster, have a significant impact on economic development and living environment in coastal areas, especially in estuary regions. This paper utilizes the Delft3D software based on a rectangular grid, driven by the eight major tidal harmonic constituents of M2, S2, N2, K2, K1, O1, P1, and Q1, to construct a hydrodynamics and sediment numerical model. The study focuses on the morphodynamic changes in the Yellow River Delta (YRD) during a severe cold wave and strong wind event. By simulating the intense cold wave from November 28 to 30, 2022, the effects on the sedimentation in the YRD were analyzed. Results show that the cold wave process increases the water levels in the nearshore areas, with a general rise of more than 0.2 m in the YRD waters, particularly severe at the old Yellow River (YR) estuary and the northwest part of Laizhou Bay, reaching 0.25-0.35 m. This increase leads to intensified erosion and sedimentation in different areas near the YR estuary, especially near the old YR estuary and in the northwest part of Laizhou Bay. After a cold wave process, the erosion and sedimentation increase significantly by 0.05-0.1m. Furthermore, by comparing the flow speed differences and tidal-induced Eulerian residual currents with and without cold waves, it was found that around the YRD, from the current river estuary to the old YR estuary, the maximum flow speed increased by more than 0.35 m/s during the cold wave, and the maximum Eulerian residual currents also increased by 0.13 m/s. The direction of the residual currents changed from northwest-southeast to south-north, further confirming the significant impact of cold waves on the morphodynamic evolution of the YRD. This study provides new perspectives and methods for understanding and predicting morphodynamic changes in estuarine regions during cold waves, which is significant for disaster prevention, mitigation, and management of estuarine areas.